O palavrão no filme “Tropa de elite: Missão Dada é Missão Cumprida” - PEREIRA, Fábio Araújo (2021)
This paper aims to present a theoretical-methodological study about the application of the swear word in the 2007´s Brazilian film "Tropa de Elite - missão dada é missão cumprida". The general objective of this work was to analyze the swear words present in the film supported by frame semantics based on the Goffnian theory, in which the word has no meaning, but function in the discourse. Goffman (1974) agrees that frames are events that vary depending on what is included in the scene. As specific objectives, this thesis discussed the swear words of the film, recording the quantity, typology and functions in which they are operated in the feature film, checking the different meanings that can be attributed to the same swear word. With the theoretical assumptions of authors like Dino Preti (1984), Fillmore (1982), Goffman (1959, 1967, 1974, 1983a, 1983b), Lakoff and Wehling (2012), Morato (2010), among others. For the scope, the swear words were observed and noted, within the context in which they were uttered. This research concluded that the expletive present in the film is conditioned to the inherent aspects of the situation. The many voices echoed in the frame are reflected in how the word is decoded. The curse word in the feature film is apprehended according to the forces acting in the context of the characters. These confronting structures form the interface of the situation, which is the most faithful definition of frame according to Erving Goffman.